2021
DOI: 10.3390/ani11061799
|View full text |Cite
|
Sign up to set email alerts
|

No Observed Adverse Effects on Health Were Detected in Adult Beagle Dogs When Fed a High-Calcium Diet for 40 Weeks

Abstract: The implications of long-term high calcium (Ca) intake are well documented in growing dogs and in adult dogs of large breed size, however, the consequences on other breeds and breed sizes are yet to be determined. Eighteen neutered adult beagles, nine males and nine females aged 1.4–4.4 years, were randomized to control or test diets providing in g∙4184 kJ−1 (1000 kcal−1): 1.44 and 7.19 total Ca balanced with 1.05 and 4.25 total phosphorus, respectively, for 40 weeks. Health parameters, ultrasound scans, radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Calcium deficiency may disturb homeostasis and lead to negative health consequences. Calcium deficiency resulting in hypocalcemia may be one of the causes of progressive lethargy, exercise intolerance, hind limb paresis, muscle atrophy and hyperesthesia12 .Research by Atwal et al13 in adult dogs shown that excess dietary calcium does not lead to adverse health effects, which means that a deficiency in the diet should be of more concern. Secondary hyperparathyroidism (NSHP), osteodystrophy and osteopenia are common complications that can occur in animals consuming an unbalanced diet.…”
mentioning
confidence: 99%
“…Calcium deficiency may disturb homeostasis and lead to negative health consequences. Calcium deficiency resulting in hypocalcemia may be one of the causes of progressive lethargy, exercise intolerance, hind limb paresis, muscle atrophy and hyperesthesia12 .Research by Atwal et al13 in adult dogs shown that excess dietary calcium does not lead to adverse health effects, which means that a deficiency in the diet should be of more concern. Secondary hyperparathyroidism (NSHP), osteodystrophy and osteopenia are common complications that can occur in animals consuming an unbalanced diet.…”
mentioning
confidence: 99%
“…Finally, faecal N concentrations were based on 19 diets from six studies (Beynen et al., 2002; Cargo‐Froom et al., 2019; De Smet et al., 1999; Forster et al., 2012; Pinna et al., 2018; Wood et al., 2004), whereas faecal P concentrations were based on 17 diets from five studies (the same, except Forster et al., 2012). Urinary N concentrations were based on two studies (Beynen et al., 2002; Castrillo et al., 2001), whereas urinary P concentrations were based on 10 diets from three studies (Atwal et al., 2021; Stevenson et al., 2003; Wood et al., 2004), including one very well‐documented study (Atwal et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…muscle atrophy and hyperesthesia 12 . Research by Atwal et al 13 in adult dogs shown that excess dietary calcium does not lead to adverse health effects, which means that a deficiency in the diet should be of more concern. Secondary hyperparathyroidism (NSHP), osteodystrophy and osteopenia are common complications that can occur in animals consuming an unbalanced diet.…”
Section: Introductionmentioning
confidence: 99%